Tables of Synodic Events from -800 to 1650 Using Modern and Almagest Models - Carman, Christian Carlos (2019)
This article describes and makes available computed data for the major synodic events for the inner (Mercury, Venus) and outer (Mars, Jupiter, Saturn) planets for the time period -800 to 1650.